Absence of rapid selection for acyclovir or penciclovir resistance following suboptimal oral prodrug therapy of HSV-infected mice - Bacon Teresa H (BMC Infectious Diseases, 2001)
Abstract Background Acyclovir (ACV) resistant herpes simplex virus (HSV) isolates can be readily selected in animal infection models receiving suboptimal ACV treatment, however no comparative studies of the emergence of resistance following suboptimal treatment with valacyclovir (VCV) or famciclovir (FCV), the prodrugs of acyclovir and penciclovir, respectively, have been reported. Methods Mice (n = 30) were infected with HSV type 1 or 2 in the ear pinnae and administered oral prodrugs at one fifth a dose previously shown to be effective. To select and amplify drug-resistant HSV, a total of seven consecutive in vivo passages with suboptimal treatment were performed for each virus sample and progeny virus from each passage was characterized by the plaque reduction (PRA) and plating efficiency assays (PEA). Results No drug-resistant HSV-2 and only a single drug-resistant HSV-1 variant were identified. Virus recovered from the first three sequential passages of this HSV-1 sample was susceptible by PRA, although the proportion of resistant virus recovered gradually increased upon passage. The resistant HSV-1 phenotype was confirmed by PRA after four sequential passages in mice. Unexpectedly, this in vivo-selected drug-resistant HSV-1 failed to yield an infection completely refractory to treatment in subsequent passages. Conclusions Sub-optimal therapy of immunocompetent mice with either VCV or FCV did not readily select for HSV-mutants resistant to either ACV or PCV, suggesting that selection of resistance with either prodrug remains difficult using this system. Futhermore, this study suggests that the PEA may represent a useful adjunct to the PRA for monitoring alterations in the proportion of drug-resistant virus even when no change in IC50 is apparent.